Meningkatkan keseimbangan dinamis dan statis pada lansia melalui latihan stabilitas inti dan berjalan tandem - Muhargianto, Dwi; Hidayatullah, M. Fuqron; Riyadi, Slamet; Mugiharto, Dwi (Universitas Nusantara PGRI Kediri, 2025)
Ageing often causes a decline in strength and balance, increasing the risk of falls in older adults. However, few studies have examined the combination of core stability exercises and paired walking and compared responses based on gender. This study presents a novel approach by applying a 2×2 factorial design to evaluate the effects of both exercises on static and dynamic balance. Forty older adults (20 men and 20 women) participated in 16 training sessions over an eight-week period. Dynamic balance was measured using the Timed Up and Go (TUG) test, while static and dynamic balance were assessed using the Berg Balance Scale (BBS). The results showed significant improvements: TUG scores decreased from 24.53 to 15.34 seconds (∆ = –9.19 seconds), indicating improved functional mobility and reduced risk of falling. On the BBS, women showed greater static improvement (+10.15 points) than men (+7.95 points), while dynamic improvement was similar in both genders. Clinically, the improvement in TUG to the safe range (<20 seconds) and the increase in BBS scores indicate a relevant improvement in postural stability for fall prevention. Overall, the combination of core stability exercises and paired walking is an effective, inexpensive intervention that can be implemented in community programs to support the mobility and functional independence of older adults.